Euphorbia antisyphilitica: Effect of growth regulators in improving growth and productivity of hydrocarbon yielding plant: Pharmaceutical Science-Branch Botany - JOHARI, SHOBHA; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2013)
Green plants use solar energy to generate reducing equivalents and incorporate atmospheric CO2 into organic molecules. Although worldwide production of biodiesel increased but still there is need to search for alternatives sources of fossil fuel. Today, ethanol and biodiesel are predominantly produced from corn kernels, sugarcane or soybean oil. However another biofuel feedstock, the latex is being explored. The race is on to optimize the technology that can produce biofuels from hydrocarbons present in latex. These hydrocarbons can be converted into petrochemicals. There is campaign, which advocates that 25% of US energy come from arable land by 2025. India is aiming 20% renewable mix by 2020. Present study has been undertaken with an object to improve latex contents of E. antisyphilitica along with its growth. Different phytohormones – IAA, NAA, GA3, CCC and 2, 4, 5-T were used to study their effect.